2006
DOI: 10.1038/sj.mp.4001866
|View full text |Cite
|
Sign up to set email alerts
|

Hyperforin prevents β-amyloid neurotoxicity and spatial memory impairments by disaggregation of Alzheimer's amyloid-β-deposits

Abstract: The major protein constituent of amyloid deposits in Alzheimer's disease (AD) is the amyloid b-peptide (Ab). In the present work, we have determined the effect of hyperforin an acylphloroglucinol compound isolated from Hypericum perforatum (St John's Wort), on Ab-induced spatial memory impairments and on Ab neurotoxicity. We report here that hyperforin: (1) decreases amyloid deposit formation in rats injected with amyloid fibrils in the hippocampus; (2) decreases the neuropathological changes and behavioral im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 70 publications
2
95
0
1
Order By: Relevance
“…Viability Assay-Viability of cells was measured by an MTT assay (39). For the MTT assay, 3.2 ϫ 10 4 primary hippocampal neurons from 18-day-old embryonic Sprague-Dawley rat brains were plated on each well of 24-well plates coated with poly-D-lysine.…”
Section: Methodsmentioning
confidence: 99%
“…Viability Assay-Viability of cells was measured by an MTT assay (39). For the MTT assay, 3.2 ϫ 10 4 primary hippocampal neurons from 18-day-old embryonic Sprague-Dawley rat brains were plated on each well of 24-well plates coated with poly-D-lysine.…”
Section: Methodsmentioning
confidence: 99%
“…Hyperforin prevents ROS release through inhibiting the activation of immune cells in rat brains (Cabrelle et al, 2008). Hyperforin has also prevented the β-amyloid induced neurotoxicity to hippocampal neurons in a rodent model by preventing the β-amyloidinduced ROS and inflammation (Dinamarca et al, 2006). A standard extract of SJW can increase the gene expression of antioxidant enzymes on rotenone-exposed rats (Sanchez- Reus et al, 2007).…”
Section: Hyperforin Protects Cg-4 Cells From Rotenone-induced Atp Depmentioning
confidence: 99%
“…Similarly, Mori et al (2013) observed that ferulic acid (30 mg/kg b.w.) reversed transgene-associated behavioral deficits and decreased brain parenchymal and cerebral vascular b-amyloid deposits and also hyperforin at 6 µM (Dinamarca et al 2006). Moon et al (2014) proved that the phenylpropanoid, 6-shogaol, at 10 mg/kg b.w.…”
Section: Bioactive Compounds With In Vivo Neuroprotectivementioning
confidence: 99%